Affect and the adoption of pro-environmental behaviour: A structural model. (December 2017) - Coelho, Filipe; Pereira, Maria C.; Cruz, Luís; Simões, Paula; Barata, Eduardo
Abstract: Pro-environmental behaviour (PEB) is an essential part of changing societies towards a more sustainable future. The literature on PEB has provided significant insights into how the anticipated emotions arising from specific ecological actions contribute to environmentally friendly conduct. Our research departs from these studies by focusing on general affect as a determinant of PEB. Moreover, we specify mechanisms for the transmission effects of trait (rather than state) affect into PEB. We use structural equation modelling to test the hypotheses, with a sample of 925 individuals. The results show that the influence of positive affect on (reported) PEB is partially mediated by environmental concern and perceived consumer effectiveness. As to negative affect, the findings suggest only a direct effect on PEB. We also found differences between males and females. These are novel results that help to illuminate the complex issue of what shapes PEB, thereby supporting relevant theoretical and practical implications. Graphical abstract: Highlights: We model the links between trait affect and pro-environmental behaviour (PEB). Structural equation modelling is used to test direct and mediated effects. The positive influence of Positive Affect on PEB is partially mediated. The negative influence of Negative Affect is only directly related to PEB. Multi-group analysis reveals significant differences between sexes.